A Quantitative 3D Motility Analysis of Trypanosoma brucei by Use of Digital In-line Holographic Microscopy - Weiße, Sebastian; Heddergott, Niko; Heydt, Matthias; Pflästerer, Daniel; Maier, Timo; Haraszti, Tamás; Grunze, Michael; Engstler, Markus; Rosenhahn, Axel (PLOS ONE, 2012)
We present a quantitative 3D analysis of the motility of the blood parasite Trypanosoma brucei. Digital in-line holographic microscopy has been used to track single cells with high temporal and spatial accuracy to obtain quantitative data on their behavior. Comparing bloodstream form and insect form trypanosomes as well as mutant and wildtype cells under varying external conditions we were able to derive a general two-state-run-and-tumble-model for trypanosome motility. Differences in the motility of distinct strains indicate that adaption of the trypanosomes to their natural environments involves a change in their mode of swimming.